Characterisation of peroxidation products arising from culinary oils exposed to continuous and discontinuous thermal degradation processes. Issue 12 (25th November 2019) - Le Gresley, Adam; Ampem, Gilbert; Grootveld, Martin; Percival, Benita C.; Naughton, Declan P.
Abstract : High-resolution NMR analysis has been used, for the first time, to identify, putatively, two new secondary aldehydic lipid oxidation products in culinary oils. Abstract : High-resolution NMR analysis has been used, for the first time, to identify, putatively, two new secondary aldehydic lipid oxidation products in culinary oils. The impact of heating and cooling times on the thermal stability, fatty acid composition and lipid oxidation product (LOP) concentrations have been analysed for continuous and discontinuous heating periods (180 °C). The susceptibility of the selected oils to thermal oxidation for the different heating episodes has been evaluated via the detection and determination of LOPs, particularly cytotoxic and genotoxic aldehydes. The identities and quantities of these LOPs evolved throughout a 2.0 hour period. Results acquired indicated that sunflower oil was more resistant to discontinuous oxidation than rapeseed and olive oils, however overall discontinuous heating resulted in more LOPs.